-X+27+3X+9=9X+225

Simple and best practice solution for -X+27+3X+9=9X+225 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -X+27+3X+9=9X+225 equation:


Simplifying
-1X + 27 + 3X + 9 = 9X + 225
Reorder the terms:
27 + 9 + -1X + 3X = 9X + 225
Combine like terms: 27 + 9 = 36
36 + -1X + 3X = 9X + 225
Combine like terms: -1X + 3X = 2X
36 + 2X = 9X + 225
Reorder the terms:
36 + 2X = 225 + 9X
Solving
36 + 2X = 225 + 9X
Solving for variable 'X'.
Move all terms containing X to the left, all other terms to the right.
Add '-9X' to each side of the equation.
36 + 2X + -9X = 225 + 9X + -9X
Combine like terms: 2X + -9X = -7X
36 + -7X = 225 + 9X + -9X
Combine like terms: 9X + -9X = 0
36 + -7X = 225 + 0
36 + -7X = 225
Add '-36' to each side of the equation.
36 + -36 + -7X = 225 + -36
Combine like terms: 36 + -36 = 0
0 + -7X = 225 + -36
-7X = 225 + -36
Combine like terms: 225 + -36 = 189
-7X = 189
Divide each side by '-7'.
X = -27
Simplifying
X = -27

You can always share this solution

See similar equations:

| -.5(x+3)(x-4)=0 | | x+x-3007=7803 | | 14k+6=92 | | 2(z-4)=-6z+56 | | 5x-6=7x+14 | | 9(5x+1)=5x-9x | | -3(x-1)(5-2x)=0 | | -3(x-4)+8=4(2x-1)-9 | | x+3x=624 | | 5s+17p=315 | | 6(5X+1)=4x-7x | | 3xs^2=27 | | -1200+j=-800 | | 3(4x+1)=2X-9X | | -5x-18 =-3 | | 2(5x+1)=5x-9x | | 0.2p=-3 | | 2(6X+1)=5x-9x | | 9j=-45 | | x+5199+x=14165 | | -17+x-4=12-8+3 | | 8y+4=4(y-7) | | -x+6=29 | | 15x^3+12x^2+9x= | | 6x+1=29-x | | -2(n-1)-(-6n-2)=3n | | 7*34= | | 4(x-2)=2(5-x) | | 5x+3=4x-18 | | 5x+3=4x-183 | | 3x+5(x-3)+8=0 | | 5(w-5)-(2w-1)=6w | | 4.1n-3.1n+0.2=-3.5+1.5 | | 14-g=32 | | -24+5c=11 | | 4m=9 | | r/0.134=1/7 | | 4x-1=8-5x | | 2x+4(x-3)=5x-1 | | x/0134=1/7 | | 6(x-5)+3(x-3)+(x-4)=4x-1 | | r/0134=1/7 | | -41b=123 | | 3y^2-2y-16= | | -30--153=x | | a+1/1/4=2/7/10 | | ln(2.25x)=0 | | 4x-12=3x-10 | | 2x-6=-3x+6-2 | | 180-x=x | | Y=-7x+13 | | 5x-7=9(x+1) | | 3x+15=150 | | 5/4=z-3/4 | | -4+4r=+5-5 | | 4z^2-4z-15= | | 3x^2+14x-10=0 | | 638366182x=638366182 | | 40-4(x+3)=7x-5 | | 5(2+3f)+3(6-f)= | | 2x^2-3x-35= | | 12+8h-10-6h= | | 4x-12=2x-4 | | -(3Y+1)-(-2Y-6)=3 | | 16y^2+8y-3= |


Related pages


how to solve 2x y 3derivative of sin cos tanroman numerals for 19902 sin 2x sinxmultiply fractions with variables calculatorwhat is the prime factorization of 125simplify cos2xf x g xgcf of 261000 1000000000square root of 529graph tanxwhat is the prime factorization of 64the prime factorization of 56twenty thousand pesos2.38 inches to fraction3x 2y 2 graphmultiplying fracconvert 625 to a fraction500-173graph of 3x 4y 129v to 6vx 7y graphgraph y 4x 8log6 191-32factor tree of 84solve y 2x-5what is 30 percent of 2800factor 3x 2 2x 24x 2y 20what is the greatest common factor of 120what is the prime factorization of 41gcf of 84how do you graph y 4xprime factorization of 7203x2 2x3what are the prime factors of 3852x 5y 0completing the square 3x 2roman numeral 79what is the square root of 2704gcf of 54 and 144find the prime factorization of 120what is the prime factorization of 3304x4 solve117-10125kg to lbssolving two step equations calculator with fractionssin of arctan12u72lwbx10what is the prime factorization of 189gcf of 84sina sinbderivate solverwhat is the prime factorization of 1184x 2y 9graph y 2cosxderivative of 3e 3xwhat is 72t52-109prime factors of 1764derivative cosxleast common factor calculatore 3lnxsin4x 1prime factorization of 440write the prime factorization of 36how to solve y 2x 5solve sin2x cos2xthe prime factorization of 49